Industrial Competitiveness through Porter's Five Forces Framework - selmiana salam; Fitriah Ningsih; Muhammad Ilham; Murtiadi Awaluddin; Sudirman (Al-Kharaj: Journal of Islamic Economic and Business, 2025)
This study explores the integration of Islamic ethical values into business competitive strategies using Porter’s Five Forces framework. The research employs a qualitative descriptive method through literature studies, drawing from academic journals, classical Islamic sources (Qur’an and Hadith), and contemporary scholars. The study examines how each of Porter’s forces threat of new entrants, bargaining power of suppliers, bargaining power of buyers, threat of substitutes, and industry rivalry can be aligned with Islamic ethical principles such as justice (‘adl), honesty (shiddiq), trust (amanah), and public benefit (maslahah). The findings indicate that integrating Islamic values can address weaknesses in Porter’s model, which is predominantly profit-oriented and economically driven. For example, ethical competition encourages market fairness and discourages monopolies; supplier and buyer relationships are guided by transparency and mutual respect; and innovation is seen as a means to serve, not to dominate. The incorporation of Islamic ethics into competitive strategy not only fosters sustainability and long-term business relationships but also transforms competition into a means of spiritual and social contribution. This approach suggests that companies operating in Muslim-majority environments or with shariah-based principles can adopt a more holistic and balanced strategy achieving competitive advantage while adhering to moral responsibilities. The study contributes to the development of Islamic strategic management literature and offers practical implications for Muslim entrepreneurs and policymakers seeking ethical and effective frameworks for industrial competitiveness.